2021
DOI: 10.21873/anticanres.15068
|View full text |Cite
|
Sign up to set email alerts
|

Lenvatinib Induces AKT/NF-κB Inactivation, Apoptosis Signal Transduction and Growth Inhibition of Non-small Cell Lung Cancer In Vivo

Abstract: Background/Aim: Non-small cell lung cancer (NSCLC) is the most common type of lung cancer with poor prognosis. Lenvatinib is a multi-kinase inhibitor that has the potential to suppress tumor progression. Our previous study suggested that lenvatinib induces cytotoxicity and apoptosis in CL-1-5-F4 cells in vitro. However, whether lenvatinib suppresses NSCLC progression in vivo remains unclear. Materials and Methods: Tumor growth inhibition and normal tissue toxicity evaluation following lenvatinib treatment were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…in vivo 37: 1991-2000 (2023) 1996 Table IV. Severity scores for pathological alterations after Nivolumab treatment (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in vivo 37: 1991-2000 (2023) 1996 Table IV. Severity scores for pathological alterations after Nivolumab treatment (19).…”
Section: Discussionmentioning
confidence: 99%
“…On day 29, we collected and isolated serum from each group of mice and stored it at -80˚C. The serums were sent to Bio-Check Laboratories (New Taipei City, Taiwan, ROC) for evaluating Aspartate Aminotransferase (AST), Alanine Aminotransferase (ALT), and gamma-glutamyl transferase (γGT) values using standardized tests (19).…”
Section: Magnetic Resonance Imaging (Mri) Scanning Of Mouse Brainmentioning
confidence: 99%
“…39 In addition, LEN has been reported to induce Akt inactivation, leading to apoptosis and growth inhibition in non-small cell lung cancer in mice. 40 Recent studies have demonstrated the involvement of these molecules in the development of NASH-related HCC. As MAFLD is defined as fatty liver with metabolic dysfunction, we further performed a stratification analysis according to metabolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…However, LEN is a tyrosine kinase inhibitor of the vascular endothelial growth factor receptor and fibroblast growth factor receptor 39 . In addition, LEN has been reported to induce Akt inactivation, leading to apoptosis and growth inhibition in non‐small cell lung cancer in mice 40 . Recent studies have demonstrated the involvement of these molecules in the development of NASH‐related HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Alamine aminotransferase (AST), alanine aminotransferease (ALT), creatinine (CREA), and gamma-glutamyl transferase (γ-GT) levels in each serum sample were quantified using analytical services provided by Axel Biotech. Inc. (Taichung, Taiwan, ROC) (29).…”
Section: Methodsmentioning
confidence: 99%